2019
DOI: 10.1111/adb.12824
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cannabinoids and their impact on neurodevelopmental processes

Abstract: Cannabinoids comprise a broad group of psychoactive substances that activate endogenous cannabinoid (EC) receptors (ie, CB 1 R and CB 2 R), altering neurotransmitter release in the brain. The importance of their regulatory role in different biological processes has prompted the development of synthetic cannabinoids (SCs), substantially more potent than tetrahydrocannabinol (THC, the main psychoactive substance of cannabis). Although SCs were primarily designed given their therapeutic applications, their recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 63 publications
0
23
0
7
Order By: Relevance
“…Similar to our findings, such results were reversed by cells' co-treatment with AM251, an inverse CB1R agonist. However, data on the impact of SCs on neuronal differentiation have been contradictory, usually depending on several distinct factors, including the cell model used, tested SC and respective concentrations, or frequency of administration [9], suggesting that the role of SCs on neuronal differentiation may be likely related to the activation of different mechanisms. In fact, others have reported that CB1R activation by the non-selective CBR agonist WIN 55,212-2 inhibited new synapse formation in rat hippocampal neurons by preventing the formation of cyclic adenosine monophosphate (cAMP) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, such results were reversed by cells' co-treatment with AM251, an inverse CB1R agonist. However, data on the impact of SCs on neuronal differentiation have been contradictory, usually depending on several distinct factors, including the cell model used, tested SC and respective concentrations, or frequency of administration [9], suggesting that the role of SCs on neuronal differentiation may be likely related to the activation of different mechanisms. In fact, others have reported that CB1R activation by the non-selective CBR agonist WIN 55,212-2 inhibited new synapse formation in rat hippocampal neurons by preventing the formation of cyclic adenosine monophosphate (cAMP) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effects of both tested SCs on neuronal differentiation depended on the activation of CB1R, suggesting that each of the SCs may induce a different response from these receptors, which requires further clarification. In fact, the involvement of CB1R in the activation of distinct signaling cascades, including the inhibition of the adenylyl cyclase (AC)-cyclic AMP-protein kinase A (PKA) pathway, activation of mitogen-activated protein kinase (MAPK) cascades, or the regulation of ion flux via inhibition of voltage-sensitive Ca2+ channels (VSCC) has already been described [9]. Moreover, it has been reported that an agonist binding to a given G protein-coupled receptor, as is the case of CBRs, can stabilize distinct receptor conformations and subsequently activate different signaling cascades that may favor one signaling pathway over the other.…”
Section: Discussionmentioning
confidence: 99%
“…They can lead to severe intoxication and death, disrupt neurodevelopmental processes, induce psychotic behavior, and lead to a rapid onset of CUD. [51][52][53] Cannabis products and synthetic cannabinoids interact with the reward system and lead to CUD through this interaction. As outlined in the previous chapter, we have a good understanding of the molecular interactions of cannabinoids with the reward system and can therefore provide mechanism-based interventions for CUD.…”
Section: Original Articlementioning
confidence: 99%
“…In addition to these, there are two other types: the endocannabinoids (naturally produced by the body) and the synthetic cannabinoids (eliciting cannabis effects, generally with a higher potency than endocannabinoids) [16]. The most important psychoactive phytocannabinoid is the delta-9-tetrahydrocannabinol (delta9THC), a partial agonist of the endocannabinoids receptors CBr1 and CBr2, the ativation of which generates central and peripheral effects [17][18][19][20][21]. The concentration of delta9THC varies in the diferent strains of cannabis (6% to 20%), and due to its physicochemical properties (small molecular size and lipophilic nature) has high distribution and transport capacity in the human body, quickly crossing the transplacental membranes [2,[22][23][24].…”
Section: Cannabis Cannabinoids and Endocannabinoid Systemmentioning
confidence: 99%
“…The effects of delta9THC are due to its action on cannabinoid receptors CBr1 and CBr2 -widely distributed throughout various organs and tissues that, together with endogenously produced cannabionids and the regulatory enzymes of synthesis and degradation, constitute the endocannabinoid system (ECS) [19,27]. The ECS is a neuromodulatory system, detected from the earliest embryonic stage and throughout preand postnal development, responsible for several controls related to the regulation of many important function, since its receptors has been found to play a key role in neuronal progenitor cell proliferation, pyramidal specification, axon pattering modulation of dendritic arbor, and promotion of neuronal differentiation [5,20,28,29]. Also, the ECS influences metabolism and physiology of multiple systems with its anabolic action, leading to protein and glycogen synthesis and fat deposition [30].…”
Section: Cannabis Cannabinoids and Endocannabinoid Systemmentioning
confidence: 99%